2014
DOI: 10.7717/peerj.493
|View full text |Cite
|
Sign up to set email alerts
|

Subtle neuropsychiatric and neurocognitive changes in hereditary gelsolin amyloidosis (AGel amyloidosis)

Abstract: Hereditary gelsolin amyloidosis (AGel amyloidosis) is an autosomal dominant form of systemic amyloidosis caused by a c.640G>A or c.640G>T mutation in the gene coding for gelsolin. Principal clinical manifestations include corneal lattice dystrophy, cranial neuropathy and cutis laxa with vascular fragility. Signs of minor CNS involvement have also been observed, possibly related to cerebral amyloid angiopathy (CAA). To investigate further if AGel amyloidosis carries a risk for a specific neuropsychological or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…GSN encodes a calcium‐dependent actin regulatory protein and is ubiquitously implicated in human health (Li, Arora, Chen, McCulloch, & Liu, ). Mutations in GSN can result in hereditary gelsolin amyloidosis, with potential for psychiatric symptoms (Kantanen, Kiuru‐Enari, Salonen, Kaipainen, & Hokkanen, ). GNAS encodes a G‐protein of importance for multiple signaling transduction pathways, including at the synapse, and has been shown to have increased expression in prefrontal cortex of suicides (Dwivedi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…GSN encodes a calcium‐dependent actin regulatory protein and is ubiquitously implicated in human health (Li, Arora, Chen, McCulloch, & Liu, ). Mutations in GSN can result in hereditary gelsolin amyloidosis, with potential for psychiatric symptoms (Kantanen, Kiuru‐Enari, Salonen, Kaipainen, & Hokkanen, ). GNAS encodes a G‐protein of importance for multiple signaling transduction pathways, including at the synapse, and has been shown to have increased expression in prefrontal cortex of suicides (Dwivedi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary gelsolin amyloidosis (HGA), also known as familial amyloidosis Finnish type, gelsolinrelated amyloidosis (AGel amyloidosis), and Meretoja disease (OMIM #105120), is a systemic amyloidosis with an autosomal dominant pattern of inheritance (1)(2)(3). HGA is characterized mainly by ophthalmological (corneal lattice dystrophy) (1,3), neurological, most typically cranial and peripheral (somatic and autonomic) neuropathy (4)(5)(6)(7)(8) and lesser central nervous system (spinal and cerebral) (9)(10)(11), and dermatological (cutis laxa) (1, 3) manifestations. Occasionally renal and cardiac signs also occur (3,12).…”
mentioning
confidence: 99%
“…Interestingly, reported patients with FAF with GSN missense mutations were usually cognitive normal. 7 27-30 Only one study reported that patients with FAF appeared slightly with abnormalities in visuocontructional and spatial performance, 31 which further confirmed the genotype-phenotype heterogeneity of the GSN gene. The phenomenon of genotype-phenotype heterogeneity has also been reported in other genes previously.…”
Section: Discussionmentioning
confidence: 93%